용융아연도금강판의 스팡글 형성에 미치는 도금욕 중 안티몬 및 납의 영향 - 김상헌(S. H. Kim); 김형민(H. M. Kim); 정원섭(W. S. Chung); 전선호(S. H. Chun) (Biuletyn Uniejowski, 2000)
Antimony in the galvanizing bath had greater effect on the growth of grains in the solidification of molten coating layer and on the decrease of its surface roughness than lead. Particularly 0.01 wt % antimony in the galvanizing bath showed much stronger effect than expected considering its low surface tension value. These effects were seemingly originated from the development of preferred orientation of (0002) plane parallel to steel surface. Antimony was found to be widely distributed in form of orderly arrangement throughout the coating layer unlike lead from the results of surface analyses on coating layers as received and on those as etched in chromating solution. In addition, supercooling in the 0.07 % antimony and the 0.2 % lead galvanizing bath was also measured to be in the range of$ 2~4^{°}C$ and $9~11^{°}C$ respectively, and it indicates that antimony forms fine dendrite expanded rapidly on the steel surface.